Roles of Whole-Genome Sequencing in Determining Transmission and Risk Factors Associated with Carbapenem-Resistant Organisms at a Vietnam HealthCare Center of Orphan Children - Van Kim Nguyen; Pirom Noisumdaeng; Katiya Ivanovitch; Eugene Athan; Larry Croft; Phuong Toai Nguyen; Huu Phuc Pham Nguyen (Microbiology Research)
Antimicrobial resistance is one of the most concerning public health issues in Vietnam due to antibiotic-resistant Gram-negative bacteria, including carbapenem-resistant organisms (CROs), which might appear in remote areas in Vietnam. At this center, we performed a cross-sectional study and collected fecal samples from humans (20 healthcare workers (HCWs) and 67 residents) and 175 environmental samples, with rectal and environment swabs, as data for this study, from September 2022 to December 2022. We conducted microbiological testing, including the MELAB Chromogenic CARBA agar plates, blood agar plates, and the BD PhoenixTM Automated Microbiology System to screen, isolate, and identify bacterial species and phenotypic tests for the antimicrobial susceptibility of carbapenem-resistant bacteria and the whole-genome sequencing for 12 CROs chosen to confirm the CRO transmission between HCWs and residents. The study findings showed that the prevalence and risk factors associated with CRO colonization were detected in HCWs, residents, and the environment in the Center of Care and Protection of Orphan Children. CRO transmission happened between HCWs and residents detected with WGS analysis. Whole-genome sequencing (WGS) plays a significant role in CRO control and prevention and reduces CRO transmission/colonization in this center and other healthcare settings.